GEOCHEMISTRY OF OILS IN THE TEREK‐CASPIAN FOREDEEP AND PRIKUMSK SWELL, NE GREATER CAUCASUS, SOUTHERN RUSSIA. (26th June 2021) - Yandarbiev, N. Sh.; Sachsenhofer, R. F.; Ajuaba, S.; Bechtel, A.; Yandarbieva, D. N.
Abstract : Hydrocarbon reserves of the order of 1140 MM brl oe have been identified in the northern foreland of the eastern Greater Caucasus, principally in the Terek‐Caspian fold‐and‐thrust belt and the Prikumsk Swell in the north of the Terek‐Caspian foredeep. Despite the great economic significance of these areas and their long exploration history, the origin of the hydrocarbons is still poorly understood. In the present paper, geochemical data from 73 oil samples representing 28 fields are used to investigate the presence of oil families and to correlate the oils with potential source rocks. Biomarker composition of oils in Cretaceous and Miocene reservoirs in the Terek‐Caspian fold‐and‐thrust belt is mainly controlled by reservoir depth (100‐5700 m) and maturity (0.70‐1.15 %Ro ), and it is therefore difficult to separate maturity and facies effects. For example, a downward increase in diasterane/sterane ratios may indicate a change in source rock facies or may be attributed to increasing maturity. Some shallow oils are biodegraded. The presence of short‐chain n‐alkanes in biodegraded oils indicates recent hydrocarbon migration. Biomarker data (e.g. the presence of oleanane) and compound‐specific isotope data suggest that the Khadum Formation in the lower part of the Maikop Group is the main source rock. However data from Cretaceous and Paleogene organic‐rich rocks, which may also have contributed to the accumulated oils, are urgently needed in order to quantify their possible input. In the Prikumsk Swell, at least two oil families, characterized by low and high C28 /C29 sterane ratios respectively, can be distinguished in reservoir rocks of Triassic to Cretaceous age. Most oils are characterized by low C28 /C29 sterane ratios and the absence of oleanane ("Group B oils"). These characteristics suggest a pre‐Upper Cretaceous source for the oils, which is also supported by the geological setting. Hierarchical cluster analysis suggests the presence of four sub‐groups (Sub‐Groups B1 to B4). Typically, biomarker ratios in oils in Cretaceous reservoirs are more uniform than those in Triassic and Jurassic reservoirs. Potential source rocks include Lower Triassic deep‐water clayey limestones and shales as well as Middle Jurassic and Aptian‐Albian marine shales. Three oil samples from Triassic and Cretaceous reservoirs form a separate oil family ("Group A"), which is genetically related to oils from the Terek‐Caspian fold‐and‐thrust belt. Group A oils have high C28 /C29 sterane ratios and in general contain at least some oleanane. A contribution by Cenozoic source rocks to Group A oils is likely.